Extended Reality in Special Education: A Bibliometric Analysis of Global Research (2015–2024) - Rullyana, Gema; Triandari, Rizki (Journal of Education and Learning Environments, 2025)
This study presents a bibliometric analysis of global research trends on the application of Extended Reality (XR) in special education from 2015 to 2024. XR, which encompasses Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR), has demonstrated considerable potential to enhance inclusive and adaptive learning for students with special needs. Drawing on data from Scopus and Web of Science, a total of 630 scientific articles were analyzed using performance analysis and science mapping techniques. The analysis revealed five major thematic clusters: (1) assistive technologies and inclusive learning, (2) technological integration and psychological dimensions of learning, (3) interventions for individuals with autism and intellectual disabilities, (4) game-based and interactive rehabilitation strategies, and (5) the application of Augmented Reality in the context of sensory disabilities. Dominant keyword nodes such as “virtual reality,” “education,” and “students” reaffirm that XR research is consistently directed toward fostering inclusive, personalized, and adaptive learning environments. Recent trends highlight growing attention to eye-tracking, wearable technologies, and adaptive user interfaces. Beyond mapping research patterns, the findings provide practical guidance for designing XR-enabled learning environments that operationalize Universal Design for Learning (UDL) principles, offering multiple means of representation, engagement, and expression to support accessibility and equity in classrooms. However, the study is limited to English-language journal articles indexed in Scopus and Web of Science, which may exclude regional publications and grey literature, particularly from the Global South. To our knowledge, this is the first bibliometric mapping of XR in special education, offering a comprehensive overview of the evolving research landscape and underscoring the need for interdisciplinary collaboration and long-term evaluative frameworks.